Exports and wages: Rent sharing, workforce composition or returns to skills? - Mario Macis; Fabiano Schivardi (Institute for the Study of Labor (IZA), 2012)
We use linked employer-employee data from Italy to explore the relationship between exports and wages. Our empirical strategy exploits the 1992 devaluation of the Italian Lira, which represented a large and unforeseen shock to Italian firms' incentives to export. The results indicate that the export wage premium is due to exporting firms both (1) paying a wage premium above what their workers would earn in the outside labor market - the rent-sharing effect, and (2) employing workers whose skills command a higher price after the devaluation - the skill composition effect. The latter effect only emerges once we allow for the value of individual skills to differ in the pre- and post-devaluation periods. In fact, using a fixed measure of skills, as typically done in the literature, we would attribute the wage increase only to rent sharing. We also document that the export wage premium is larger for workers with more export-related experience. This indicates that the devaluation increased the demand for skills more useful for exporting, driving their relative price up.
urn:nbn:de:101:1-201208065487
Keywords: F16; J31; 330; export wage premium; linked employer employee data; Lohnstruktur; Export; Qualifikation; Abwertung; Schätzung; Italien